Non-secretory myeloma: clinical profile and diagnostic utility of immunohistochemistry and free light chain assay in a rare variant of plasma cell myeloma - Monal Trisal; Anamika Rawat; Jyoti Mishra; Kangana Sengar; Sanjay Kumar Mishra (MGM Journal of Medical Sciences)
Background: Non-secretory multiple myeloma (NSMM) is a rare variant of multiple myeloma (MM), characterized by the absence of detectable monoclonal (M) protein in both serum and urine, as determined by standard electrophoresis and immunofixation techniques. This condition presents significant diagnostic and monitoring challenges, often necessitating the use of advanced investigative tools. Objectives: The objectives of the study were to detail the clinical and hematological profile of NSMM, focusing on the diagnostic value of immunohistochemistry (IHC), and serum free light chain (sFLC) assays and to assess treatment response and clinical outcomes. Materials and Methods: A retrospective study was conducted over a 3-year period at a tertiary care center. Patients who presented with the clinical features indicative of MM but lacked detectable M-protein on high-resolution serum electrophoresis (HRSE) and urine protein electrophoresis (UPEP) were included in the study. The diagnostic evaluation included complete blood counts, biochemical testing, sFLC assay, bone marrow aspiration and biopsy with IHC (CD138, kappa, and lambda), and imaging (MRI/PET-CT). Patients with positive serum or urine immunofixation or those exhibiting features of MGUS or smoldering myeloma were excluded from the study. Results: Among 100 evaluated MM cases, 4 (4%) were identified as NSMM. The median age was 56 years (range: 49–62), with a predominance of males (male-to-female ratio 3:1). All patients reported bone pain, and 75% presented with anemia. Imaging studies showed lytic bone lesions in all cases. Bone marrow plasma cell infiltration ranged from 35% to 75%. All cases were CD138-positive, and cytoplasmic kappa or lambda light chain restriction was observed in three patients. sFLC abnormalities were noted in three cases, indicating a non-secretory pattern. Treatment response and prognosis were similar to those of secretory myeloma when standard therapeutic protocols were used. Conclusion: Although rare, NSMM necessitates a high level of clinical awareness and a thorough diagnostic approach. True non-secretory myeloma typically presents with normal serum free light chain (sFLC) levels and kappa/lambda ratios. In contrast, hyposecretory myeloma exhibits elevated levels of involved light chains and abnormal ratios despite negative results on SPEP and UPEP. Bone marrow analysis and immunophenotyping are essential for detecting clonal plasma cells and confirming the diagnosis. Clinically and therapeutically, NSMM resembles secretory myeloma despite the absence of measurable M-protein.